Role of bronchoscopy in management of central squamous cell lung carcinoma in situ - Gupta, Ankit (Ann Transl Med, 2019)
Squamous cell carcinoma in situ (SCIS) is the pre-invasive stage of squamous cell carcinoma. Early detection and management of SCIS can prevent further progression. Although surgery and external beam radiation therapy are treatment options for SCIS, smaller lesions can be easily managed by bronchoscopic modalities like photodynamic therapy (PDT), cryotherapy, mechanical debulking with biopsy forceps, electrocautery and argon plasma coagulation (APC). Endobronchial brachytherapy (EBBT) and lasers may be judiciously utilized in selected cases. Although, previous studies of treatment modalities may have inadvertently included cases of invasive carcinomas, the advent of new technologies like radial probe endobronchial ultrasound (RP-EBUS) and optical coherence tomography (OCT) can help accurately determine the of depth of invasion. Superficial extent can also be better demarcated with techniques like auto-fluorescence bronchoscopy and narrow band imaging (NBI). New drugs for PDT with deeper penetration and less phototoxicity are being developed. These advances hopefully will allow us to perform superior clinical trials in future and improve our understanding of diagnosis and management of SCIS.